Radiographic analysis of teeth calcification of breastfed rat cubs of mothers consuming excessive Arabica coffee - Apriyono, Dwi Kartika; Shita, Amandia Dewi Permana; Fatimatuzzahro, Nadie; Prasetya, Rendra Chriestedy; Umaimah, Ulfa (Majalah Kedokteran Gigi Indonesia, 2023)
Lack of nutrient intake, especially calcium, can inhibit tooth development because calcium is the major component of the inorganic material that forms enamel and dentin. Caffeine in coffee can decrease calcium levels in the body. Arabica coffee has a very high caffeine content compared to other types of coffee. Excessive caffeine consumption can cause the inhibition of PTH secretion. As a result, the nursing mother's body cannot absorb calcium optimally. This makes the baby lack calcium intake which is used for the dental calcification process. This study analyzes radiographic images of tooth calcification of rat cubs during lactation period from rat mothers which consumed excess doses of Arabica coffee. Forty-eight breastfeeding rat mothers (n = 48) were divided into a control group and a treatment group. The control group consisted of 24 rat mothers that were given aquadest. The treatment group consisted of 24 nursing rat mothers, which were given coffee orally at a dose of 2.7 grams/200 grams/day. After the rat mothers gave birth (H + 1 to H + 18), every 4 rat cubs were euthanized, then the mandibular bones were X-rayed. Dental calcification was viewed and analyzed based on radiographic images. The teeth of rat cubs whose mothers consumed excess doses of Arabica coffee experienced a delay in the calcification stage compared to the teeth of normal rat cubs. Consumption of Arabica coffee by nursing mothers can cause a delay in the stage of dental calcification in rat cubs.